Contextualising curriculum through issues-based approaches: a case of eco-schools in Kenya - Epus, Joash Gregory Odeke (Rhodes University, Faculty of Education, Department of Education, 2010)
This study involved an issues-based approach to curriculum contextualisation in the context of the Eco-Schools programme in Kenya. It adopted a two-phase design using interpretivist and socially critical research orientations. In this study, research is represented as a process which is socially constructed within a particular theoretical, contextual, social and historical context by unfolding the thesis to illuminate how the phases are closely woven into each other. The first phase used the survey method for a contextual review of existing approaches and views relating to environmental education in the formal education sector. The survey aimed to develop a deeper understanding of environmental education as currently practiced in Kenya and to unravel the complexities surrounding it. It involved about two hundred and six primary school teachers and a critical review of a set of resource materials used in Kenyan Primary Schools. It revealed that some aspects of environmental education practice and the prevailing technocratic view of curriculum in Kenyan primary schools potentially limit possibilities for issues-based approaches to curriculum contextualisation. The action research process in four case study schools in Nyanza province of Kenya represent an attempt to address issues in context through socially critical environmental education. Participant observations, workshops and document analysis revealed that, contextualised conceptions of the terms 'environment' and 'environmental education' that resulted from a process of deliberation of meaning by teachers in relation to their contexts and practices served to set perspective for the action research process. Further, the planning phase which involved environmental auditing to identify issues of concern, prioritization of actions, issues to address, and action planning to guide implementation was critical in setting the agenda of the action research process in each of the case study schools. Integration and infusion of local issues of concern into curriculum planning further enriched processes of curriculum contextualisation, making them relevant to local contexts by addressing real issues through appropriate pedagogical approaches in auditing, investigation and research, communicating and interpreting results, reflecting on investigations and taking action. The action research process further enhanced cooperation and partnership between the case study schools and surrounding communities with mutual benefits. The research report demonstrates that despite the limitations posed by the technocratic orientation of the Kenyan curriculum, it is possible to address real environmental issues, risks and associated sustainable development challenges in context through issues-based approaches to curriculum contextualisation in the context of the Eco-Schools programme.
Keywords: Environmental education -- Kenya -- Case studies; Curriculum planning -- Kenya -- Case studies; Curriculum change -- Kenya -- Case studies; Environmental literacy -- Study and teaching -- Namibia -- Case studies; Environmental education -- Activity programs -- Namibia -- Case studies; Conservation of natural resources -- Study and teaching -- Namibia -- Case studies